The Role of Circular RNAs in Immune-Related Diseases - Xie, Rou; Zhang, Yongxin; Zhang, Jun; Li, Jing; Zhou, Xikun (Frontiers in Immunology, 2020)
Circular RNAs (circRNAs) are a novel class of RNAs with a covalently closed loop structure without a 3’ polyadenylation (poly-(A)) tail or a 5’ cap. They used to be considered as the occasional and useless products of RNA splicing errors because they could not be detected by traditional RNA sequencing technology. Benefiting from the development of specific biochemical and computational approaches, researchers showed that circRNAs are universally expressed and functional. Further studies have revealed their important functions regarding regulating gene expression at the transcriptional and post-transcriptional levels. These functions include acting as microRNA (miRNA) sponges, binding to RNA-binding proteins (RBPs), acting as transcriptional regulatory factors, and serving as translation templates. The advances in circRNA research has opened researchers’ eyes to a new area of research on the roles of circRNAs in the pathogenesis of various diseases, especially at the immune level because of the close relationship between circRNAs and the immune response. Emerging research indicates that circRNAs could act as potential biomarkers related to diagnosis, therapeutic effects, and prognosis, and they may be effective therapeutic targets in immunological disorders, including certain diseases that are currently difficult to treat.